1893 Ariz. Sess. Laws 12 - (:unkn) unknown (My University, 1893)
An Act To Regulate And Prohibit The Carrying Of Deadly Weapons Concealed, § 1: Prohibited the concealed carry any pistol, other firearm, dirk, dagger, slung-shot, sword cane, spear, brass knuckles, or other knuckles of metal, Bowie-Knife, or any kind of knife not manufactured and used for the purpose of offense or defense.
Keywords: CARRY - CONCEALED